2003
DOI: 10.1259/bjr/65778215
|View full text |Cite
|
Sign up to set email alerts
|

Radiation doses to the legs of radiologists performing interventional procedures: are they a cause for concern?

Abstract: The purpose of this study was to ascertain the magnitude and distribution of doses to the legs of radiologists when performing interventional procedures. LiF:Mg,Ti TLD100 chips were used to measure simultaneously doses to the lower limbs and, for comparison, the hands during 100 interventional procedures. Results show leg dose was dependent upon type and complexity of procedure, equipment used and whether lead protection was available. Where no lead protection was used, the doses to the lower limbs were freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 14 publications
2
31
0
Order By: Relevance
“…In IR, the highest doses were recorded in vertebroplasty (5239 mSv at the left wrist and 1129 mSv at the eyes) and TIPSS (1959 mSv at the left leg). However, doses associated with these procedures are likely to be high, as they are commonly the longest procedures undertaken and require the use of several different projections [17,18]. Additionally, in these procedures the physicians need to be close to the patient's side in an area of relatively high scatter dose rate in order to manipulate the catheter effectively [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In IR, the highest doses were recorded in vertebroplasty (5239 mSv at the left wrist and 1129 mSv at the eyes) and TIPSS (1959 mSv at the left leg). However, doses associated with these procedures are likely to be high, as they are commonly the longest procedures undertaken and require the use of several different projections [17,18]. Additionally, in these procedures the physicians need to be close to the patient's side in an area of relatively high scatter dose rate in order to manipulate the catheter effectively [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, doses associated with these procedures are likely to be high, as they are commonly the longest procedures undertaken and require the use of several different projections [17,18]. Additionally, in these procedures the physicians need to be close to the patient's side in an area of relatively high scatter dose rate in order to manipulate the catheter effectively [17]. Because of the nature of the interventional procedures, which involve manipulation of devices through catheters, it is impossible to avoid the hands being exposed to radiation scattered from the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Readers are directed to the extensive work in the literature [2,[54][55][56]. The magnitude and distribution of scattered radiation are affected by many factors, including patient size, gantry angulation, patient position, filtration, fluoroscopic settings, and the use of shielding.…”
Section: Scattermentioning
confidence: 99%
“…Although some studies found some good correlation between staff doses and DAP values (3,8,11) , generally a wide range of radiation exposure relative to patient dose is found (5,10,12) . The bad correlation can be explained by different parameters that affect the extremity doses such as protective devices and especially different protocols followed by the staff.…”
Section: Use Of Extremity Dosemeters In Interventional Proceduresmentioning
confidence: 96%
“…For other interventional procedures (embolisation, stent placements and vertebroplasty), following range of hand doses are reported (6 -9) : 50-630 mSv per procedure. If lead protection is not used, the dose to the feet may range from 320 to 2640 mSv per procedure, which exceeds the hand exposure during the same procedure (8) . Studies (3,4,7,10) on IC procedures (CA, PTCA and ablations) report shoulder doses between 10 and 100 mSv per procedure, feet doses between 10 and 200 mSv per procedure and hand doses between 260 and 350 mSv per procedure.…”
Section: Use Of Extremity Dosemeters In Interventional Proceduresmentioning
confidence: 99%